The Concept of Time According to Thomas Aquinas - Aleksandravičius, Povilas (Problemos, 2009)
The article explains Thomas Aquinas’ concept of time on the basis of his metaphysics of being. At the same time, it shows the distance between his concept and the Aristotle’s conception of time, despite the fact that, formally, both thinkers used the same definition of time. The article analyzes the main elements of this definition through their interaction: time, motion and human soul. The journey from the Aristotle’s ontology of substances (υοσία) to the Thomistic metaphysics of the act of being (actus essendi) uncovers the unity among between motion, human soul and the acts of being of time. Nurtured by the act of divine creation, time appears as a tension, as the human soul itself, which ‘measures’ the ontological movement of a being and makes continuous its continual moments of beginning, by adding the dimensions of past and future.